2008
DOI: 10.1073/pnas.0801030105
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3A genotype is strongly associated with human longevity

Abstract: Human longevity is a complex phenotype with a significant familial component, yet little is known about its genetic antecedents. Increasing evidence from animal models suggests that the insulin/ IGF-1 signaling (IIS) pathway is an important, evolutionarily conserved biological pathway that influences aging and longevity. However, to date human data have been scarce. Studies have been hampered by small sample sizes, lack of precise phenotyping, and population stratification, among other challenges. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
703
5
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 863 publications
(733 citation statements)
references
References 64 publications
14
703
5
11
Order By: Relevance
“…ASXL2 is a polycomb group protein with known functions in development that has also been associated with pediatric cancer, but to our knowledge has not before been suggested as a longevity gene (Huether et al ., 2014). The SNP in the known longevity gene FOXO3 has not only been previously associated with reduced fasting insulin and HOMA‐IR (Willcox et al ., 2008), but here it was found to produce lower circulating IGF‐I levels. Multiple genetic determinants for circulating IGF‐I in normal and IGF1R resistance states might partially explain the U‐shaped association of circulating IGF‐I concentration with mortality (Suh et al ., 2008; Burgers et al ., 2011).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…ASXL2 is a polycomb group protein with known functions in development that has also been associated with pediatric cancer, but to our knowledge has not before been suggested as a longevity gene (Huether et al ., 2014). The SNP in the known longevity gene FOXO3 has not only been previously associated with reduced fasting insulin and HOMA‐IR (Willcox et al ., 2008), but here it was found to produce lower circulating IGF‐I levels. Multiple genetic determinants for circulating IGF‐I in normal and IGF1R resistance states might partially explain the U‐shaped association of circulating IGF‐I concentration with mortality (Suh et al ., 2008; Burgers et al ., 2011).…”
Section: Discussionmentioning
confidence: 53%
“…In animal models, diminished IGF‐I/insulin signaling has been associated with extended lifespans (Ziv & Hu, 2011), although the role of the IGF axis in human longevity remains inconclusive. Human genetic studies have suggested an association between polymorphisms in IGF‐I signaling pathway genes and longevity (Willcox et al ., 2008; Ziv & Hu, 2011; Di Bona et al ., 2014). Heritability studies have provided evidence for a substantial genetic contribution to circulating concentrations of IGF‐I (with heritability estimates ~40–60%) and IGFBP‐3 (80%) (Harrela et al ., 1996; Hong et al ., 1996; Souren et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is a complex biological process with multiple contributing genetic pathways (Kenyon et al ., 1993; Lakowski & Hekimi, 1996; Hansen et al ., 2007; Lunetta et al ., 2007; Pan et al ., 2007; Willcox et al ., 2008; Li et al ., 2009; Imai & Guarente, 2014; Satoh & Imai, 2014), significant variation among even closely related organisms (Jones et al ., 2014), and an ongoing debate about its root causes and origin (Kirkwood, 2005). At its core, however, aging is simply the statistical phenomenon of an increased probability of death over time.…”
Section: Introductionmentioning
confidence: 99%
“…Despite more than 20 years of research into the genetic basis of human longevity, only alleles in the APOE and FOXO3 genes have repeatedly been shown to be associated with survival to very advanced ages (Schächter et al ., 1994; Willcox et al ., 2008; Flachsbart et al ., 2009; Soerensen et al ., 2010; Deelen et al ., 2013). APOE and FOXO3 were initially detected in candidate‐driven case–control investigations, but APOE has since then been confirmed in a number of genome‐wide association studies (GWAS).…”
mentioning
confidence: 99%